Application of Design Thinking and Chemical Analysis of the Taro Chip Industry in Several Taro Chip Industries in Padang Panjang City - Amelia Sari, Dice; Kasim, Anwar; Kasim, Fitriani (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
Taro is an important source of carbohydrates, providing 23.7 g per 100 g of raw taro, but its potential use has not been fully realized, one option for its utilization is to produce taro chips. This research aims to use design thinking methodology to create an innovative product development strategy aligned with market demand. The research strategy is to improve the business through design thinking techniques. According to the survey results, the packaging used is in the form of a standing pouch, which features a naturally random shape of taro chips and a citrus leaf balado flavor variant on the chips created through design thinking. Chemical analysis of the taro chips revealed a moisture content of 5.08%, ash of 1.62%, protein of 3.08%, fat of 26.67%, and carbohydrate of 63.56%, following the SNI 01-4305-1996 standard. Contribution to Sustainable Development Goals (SDGs)SDG 2: Zero hunger SDG 3: Good Health and Well-beingSDG 8: Decent Work and Economic GrowthSDG 9: Industry, Innovation, and Infrastructure SDG 12: Responsible Consumption and Production